SOME FEATURES OF THE DISTICH AS A STROPHIC UNIT IN THE UKRAINIAN SYLLABIC VERSE OF THE EIGHTEENTH CENTURY - Valentyn MALTSEV (Актуальні питання суспільних наук та історії медицини, 2020)
The article outlines the problem of the place of the distich as a strophic unit in the binary opposition ―strophic – astrophic‖ verse, as well as considers several options for diversification from a clear two-verse structure with a constant double rhyme. Research methods: formal-statistical, comparative and descriptive. Scientific novelty. Analysis of the material and poetic research allows us to conclude that there is every reason to interpret the vast majority of poetic texts with a continuous double rhyme as strophic two-verse derivations. At the same time, in such texts can be noticed different ways of enrichment, diversification of such a simple strophic structure. Conclusions. There are cases of